The Secret of Baobab's (Adansonia spp., Malvaceae) longevity - Shafa Nashrullah; Waki'atil Rosida; Dhea Athariqa Salsabila; Mukhamad Su'udi (Lilloa)
The Baobab (Adansonia spp.) is known as the "tree of life", renowned for its longevity, whit individuals that can survive for thousands of years. This article reviews various baobab adaptations supporting their survival and longevity, encompassing morphological and physiological mechanisms in the seedling phase, water storage in stems, and resistance to extreme environmental conditions. Baobabs also exhibit special adaptive mechanisms, such as stomatal regulation, UV resistance, and antibacterial properties. In addition, the heat-resistant morphology of the baobab fruit and the hard skin play an important role in preserving seeds from forest fires and dispersing them through various means. This study emphasizes that baobab's unique adaptations not only support their sustainability but also provide significant potential for the conservation and study of plant survival under extreme environmental conditions.